BAHAYA PAPARAN PESTISIDA TERHADAP KESEHATAN MANUSIA - Oktofa Setia Pamungkas (BIOEDUKASI, 2016)
Pesticides are chemicals we use in almost everyday chorus. In addition to their beneficial uses, the active ingredient of pesticides is also a source of toxins that harm human health. Pesticide poisoning effect on the work of organs and organ systems. Intake of pesticide poisonings can occur consciously or unconsciously through the skin, respiratory and orally. Symptoms of pesticide poisoning is characterized by a decrease in the level of health condition from mild to severe, even so an accurate diagnosis requires a definite medical process.. Keywords: pesticides poisoning,human health